MODULAR PARTIES PADA CALON LEGISLATIF DI KABUPATEN BADUNG STUDI KASUS : I MADE SURYANANDA PRAMANA - I Gusti Ayu Yoyik Anna Midori; I Ketut Putra Erawan; Kadek Dwita Apriani (Jurnal Ilmiah Widya Sosiopolitika, 2025)
This study analyzes the strategic shift from patron client relations to modular parties in the election of I Made Suryananda Pramana to the Badung Regency DPRD in 2019 and 2024. Using a qualitative case study approach, the research revealsthat the candidate leveraged local actors such as customary leaders and banjar structures as semi autonomous political brokers to efficiently mobilize votes. Although the total vote count decreased in 2024, this strategy successfully consolidated the core support base through material incentives facilitated by party elites. The study concludes that this electoral success resulted from integrating elite political capital with modular strategies responsive to the local Balinese socio cultural context.